2013
DOI: 10.1371/journal.pone.0069082
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Never-Medicated Bipolar Disorder Patients towards Development and Validation of a Peripheral Biomarker Profile

Abstract: There are currently no biological tests that differentiate patients with bipolar disorder (BPD) from healthy controls. While there is evidence that peripheral gene expression differences between patients and controls can be utilized as biomarkers for psychiatric illness, it is unclear whether current use or residual effects of antipsychotic and mood stabilizer medication drives much of the differential transcription. We therefore tested whether expression changes in first-episode, never-medicated BPD patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The majority of studies have focused on schizophrenia-spectrum psychosis, suggesting alterations in genes related to myelination, neurodevelopment and AKT pathway, 14 although affective psychoses studies are under-represented in the literature, particularly early-stage affective psychoses. Very few studies on gene expression of antipsychotic-naive bipolar disorder patients have been conducted, 15 , 16 , 17 , 18 reporting alterations in inflammatory genes, such as TNF , 15 and in genes of AKT1/mTOR pathway. 18 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have focused on schizophrenia-spectrum psychosis, suggesting alterations in genes related to myelination, neurodevelopment and AKT pathway, 14 although affective psychoses studies are under-represented in the literature, particularly early-stage affective psychoses. Very few studies on gene expression of antipsychotic-naive bipolar disorder patients have been conducted, 15 , 16 , 17 , 18 reporting alterations in inflammatory genes, such as TNF , 15 and in genes of AKT1/mTOR pathway. 18 …”
Section: Introductionmentioning
confidence: 99%
“…NUCKS1 directly interacts with miR-92a-3p and miR-29b-3p in BD patients [ 62 ]. Meanwhile, in in vitro studies, NUCKS1 is downregulated upon enforced expression of miR-125b in combination with miR-99a and/or miR-100 compared with scrambled control-miR in ALL [ 57 ].…”
Section: Functions Of Nucks1 In Diseasesmentioning
confidence: 99%
“…A peripheral gene expression biomarker panel was developed based on global leukocyte gene expression changes in first-episode and nevermedicated BPD patients compared to currently medicated BPD patients and matched healthy controls. The 10-gene model exhibited a diagnostic accuracy of 84% (89% sensitivity and 75% specificity; p < 0.001) [239]. Lowthert et al (2012) reported that 127 genes were differentially expressed in lithium responders versus non-responders in depressed BD patients after 8 weeks of treatment, with an upregulation of apoptosis regulatory genes [240].…”
Section: Peripheral Gene Expressionmentioning
confidence: 99%